2023
DOI: 10.3389/fphar.2023.1082817
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria as novel mediators linking gut microbiota to atherosclerosis that is ameliorated by herbal medicine: A review

Abstract: Atherosclerosis (AS) is the main cause of cardiovascular disease (CVD) and is characterized by endothelial damage, lipid deposition, and chronic inflammation. Gut microbiota plays an important role in the occurrence and development of AS by regulating host metabolism and immunity. As human mitochondria evolved from primordial bacteria have homologous characteristics, they are attacked by microbial pathogens as target organelles, thus contributing to energy metabolism disorders, oxidative stress, and apoptosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 282 publications
(314 reference statements)
1
11
0
Order By: Relevance
“…[50] Furthermore, an imbalance in gut microbiota and inflammatory responses stimulate the immune response of the body and participate in the process of atherosclerosis. [51] Emoto et al [52] showed that the F/B ratio is directly proportional to body weight. In addition, increased lipid absorption from food is linked to increased firmicute abundance, which can lead to obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[50] Furthermore, an imbalance in gut microbiota and inflammatory responses stimulate the immune response of the body and participate in the process of atherosclerosis. [51] Emoto et al [52] showed that the F/B ratio is directly proportional to body weight. In addition, increased lipid absorption from food is linked to increased firmicute abundance, which can lead to obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Current research has revealed that the gut microbiota regulates the secretion of mitochondrial reactive oxygen species, generation of immune cell inflammatory factors, and the inflammatory state by affecting the NF‐κB pathway [50] . Furthermore, an imbalance in gut microbiota and inflammatory responses stimulate the immune response of the body and participate in the process of atherosclerosis [51] . Emoto et al [52] .…”
Section: Discussionmentioning
confidence: 99%
“…6 According to some evidence obtained by animal studies, Olibanum and its constituent, boswellic acid have obvious positive effects on neuroinflammation diseases and they could be useful in improving a variety of models of cognitive dysfunction and memory impairment caused by hypothyroidism, diabetes, seizure, and stroke. 7 Olibanum is traditionally used in Iran for pregnant women during the first trimester to enhance the learning ability of the child. 34 To the best of our knowledge, this is the first clinical trial that investigated the effect of Olibanum on memory function.…”
Section: Discussionmentioning
confidence: 99%
“…Olibanum inhibits inflammation in many inflammatory diseases by specifically inhibiting 5‐lipooxygenase enzyme, preventing leukotriene synthesis and stopping glycosaminoglycan production 6 . According to some evidence obtained by animal studies, Olibanum and its constituent, boswellic acid have obvious positive effects on neuroinflammation diseases and they could be useful in improving a variety of models of cognitive dysfunction and memory impairment caused by hypothyroidism, diabetes, seizure, and stroke 7 . Olibanum is traditionally used in Iran for pregnant women during the first trimester to enhance the learning ability of the child 34…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation